Coral reef management in Malaysia: conservation strategies after AGENDA 21 - Muzneena, A.M.,; Othman, B.H.R.,; Sharina Shaukat,; Tukimat Lihan, (Environmental Management Society, Malaysia, 2001)
Coral reef ecosystems are among the most species diverse, complex and beautiful ecosystems. Coral reef serves many functions to humans either commercially, recreationally, aesthetically or environmentally. However these ecosystems are under increasing pressure and are in serious decline globally. It has been estimated that 10 percent of the earth’s coral reefs have already been seriously degraded and a much greater percentage is threatened. Coral reefs of Malaysia suffer from anthropogenic stresses and also natural disturbances. Provisions for the protection and management of islands and the surrounding aquatic resources in Malaysia is found in relevant legislation such as the Exclusive Economic Zone Act (Act 311), the Fisheries Act 1985 (Act 317), the Continental Shelf Act 1966 (Act 83) and the Environmental Quality Act 1974 (Act 127). Management measures currently taken should ensure the continued preservation of the biological diversity of coral reef ecosystem in Malaysia. All reefs in peninsula Malaysia region are expected to decline significantly in the next 20 years as a result of sedimentation and water pollution. Meanwhile reefs off Sabah are experiencing overexploitation. The 1992 United Nations Conference on Environment and Development (UNCED) under Agenda 21, Chapter 17 specifically mentioned coral reefs as one of the marine ecosystems of high levels of biodiversity and productivity and should be accorded high priority for identification and protection. Several strategies under Agenda 21, Chapter 17 should be considered and implemented to ensure effective conservation and sustainable use of the coral reef in Malaysia. The strategies are to implement integrated coastal zone management; improve coral reef ecosystem monitoring, database collection, restoration and scientific understanding; strengthen legal and regulatory framework and finally increase awareness on the importance of coral reef ecosystems